The potential of biogas production and effects of alfalfa silage under the synergistic influence of Lactobacillus acidophilus and Rosa roxburghii pomace waste on the fermentation quality and bacterial community - Maoya Li; Jiachuhan Wang; Qiming Cheng; Zhongfu Long; Chao Chen; Yixiao Xie; Yao Lei; Yulian Chen; Yuanyuan Zhao; Xiangjiang He; Wei Yan; Zhijun Wang (mSphere)
ABSTRACT The process of ensiling serves as a dual-purpose technique, functioning as a means of preserving biomass for biogas production while serving as a biological pretreatment method with the potential for little fermentation loss. In this study, we investigate the potential of Rosa roxburghii pomace (RP) and Lactobacillus acidophilus to improve the biomass preservation of biogas produced from alfalfa during anaerobic storage. Coinoculation of RP and Lactobacillus acidophilus resulted in better preservation of nutrients (biomass), with a significant increase of 47.38% within the lactic acid content and a notable decline of 40.34% in the ammonia nitrogen content relative to those in the control treatment. Moreover, coinoculation of RP and Lactobacillus acidophilus resulted in an elevated proportion of Lactobacillus, and the species Lactiplantibacillus plantarum dominated anaerobic fermentation. The synergistic effect of RP and Lactobacillus acidophilus continuously stimulated anaerobic fermentation, leading to 33.33% and 23.17% increases in methane production and acetate content, respectively, after 72 h of coinoculation with RP and Lactobacillus acidophilus compared to the control treatment. Overall, coinoculation of RP and Lactobacillus acidophilus offers an attractive opportunity to increase methane production from fruit waste while reducing costs and synergistically integrating with other pretreatment techniques to optimize the methane generation potential.IMPORTANCEConsidering the increasing global energy demand and urgent environmental issues, exploring prospective resources for bioenergy production is imperative. However, the biomass of legume perennials may serve as an inexpensive and stable source of clean energy for modern society due to its wide availability and broad range of sources. In addition, the combination of RP and Lactobacillus acidophilus application increased the abundance of Lactobacillus, inhibited the growth of Kosakonia, and promoted anaerobic fermentation, which had beneficial synergistic effects on biomass retention and biogas production in alfalfa samples. Coinoculation improvements with RP and Lactobacillus acidophilus observed here are expected to reduce costs associated with CH4 conversion bioprocesses and increase CH4 production.